Atomic‐Monolayer MoS2 Band‐to‐Band Tunneling Field‐Effect Transistor. Issue 41 (4th September 2016) - Lan, Yann‐Wen; Torres, Carlos M.; Tsai, Shin‐Hung; Zhu, Xiaodan; Shi, Yumeng; Li, Ming‐Yang; Li, Lain‐Jong; Yeh, Wen‐Kuan; Wang, Kang L.
Abstract : The experimental observation of band‐to‐band tunneling in novel tunneling field‐effect transistors utilizing a monolayer of MoS2 as the conducting channel is demonstrated. Our results indicate that the strong gate‐coupling efficiency enabled by two‐dimensional materials, such as monolayer MoS2, results in the direct manifestation of a band‐to‐band tunneling current and an ambipolar transport.